ON EXISTENCE AND CONSTRUCTION OF A GENERAL POLYNOMIAL SOLUTION OF A CLASS OF SECOND ORDER DIFFERENTIAL EQUATIONS’ SYSTEMS - Piperevski, Boro (Matematichki Bilten, 2001)
Theorem. Havіng \(ABCD(AD-BC) e 0\) the systеm (1) has a polynomial solution, iff \(n,mN\) exist, such that (9) for something \(p{0,1,2,…,m-2}\). In this case the polynomial solution of the systеm (1) will be given by the formula (10).